1990
DOI: 10.1021/ic00345a045
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on rhenium and tungsten halo trialkylphosphine, M2X4(PR3)4 compounds (M = rhenium, tungsten; X = Cl, Br; R = Me, n-Pr, n-Bu). The first examples of simple three-way disorder of dimetal units within ordered ligand cages

Abstract: The following, previously known, multiply bonded dirhenium and ditungsten compounds have been characterized by X-ray crystallography: Re2C14(PMe3)4 (l), [RezC14(PMe3)4]Re04 (2), RezC14(P-n-Pr3)4 (3), Re2Br4(P-n-Pr3)4 (4), and W,CI,(P-n-B u~)~C~H~ (5). Pertinent crystal data are as follows: for 1, monoclinic space group C2/c, a = 18.058 (3) A, 6 = 9.247 (1) A, c = 18.725 (2) A, 0 = 124.64 (I)', V = 2572 (1) A3, Z = 4; for 2, orthorhombic space group Pmcn, a = 14.166 (2) A, b = 9.799 (2) A, c = 20.836 (4) A, V =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 8 publications
(12 reference statements)
3
9
0
Order By: Relevance
“…The average Re–Br (i.e., 2.504(1) Å) and Re–P (i.e., 2.420(2) Å) distances in Re 2 Br 4 (PMe 3 ) 4 are respectively ∼0.08 and 0.05 Å shorter than in Re 2 Br 4 (P- n -Pr 3 ) 4 ; these differences are presumably due to steric effects induced by the bulkier phosphine ligand. The Re–P distance in Re 2 Br 4 (PMe 3 ) 4 is similar to the one found in Re 2 Cl 4 (PMe 3 ) 4 (i.e., 2.417(2) Å) . The Re–Br and Re–P distances are both slightly shorter by ∼0.02 Å than the Tc–Br and Tc–P distances in Tc 2 Br 4 (PMe 3 ) 4 (Table ).…”
Section: Results and Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The average Re–Br (i.e., 2.504(1) Å) and Re–P (i.e., 2.420(2) Å) distances in Re 2 Br 4 (PMe 3 ) 4 are respectively ∼0.08 and 0.05 Å shorter than in Re 2 Br 4 (P- n -Pr 3 ) 4 ; these differences are presumably due to steric effects induced by the bulkier phosphine ligand. The Re–P distance in Re 2 Br 4 (PMe 3 ) 4 is similar to the one found in Re 2 Cl 4 (PMe 3 ) 4 (i.e., 2.417(2) Å) . The Re–Br and Re–P distances are both slightly shorter by ∼0.02 Å than the Tc–Br and Tc–P distances in Tc 2 Br 4 (PMe 3 ) 4 (Table ).…”
Section: Results and Discussionsupporting
confidence: 73%
“…Steric effects induced by the halogen ligands are presumably the cause of these differences. The Re–Re separation is similar to the one found in Re 2 Br 4 (P- n -Pr 3 ) 4 (i.e., 2.253(4) Å) and indicates that the nature of the phosphine has a minor effect on the metal–metal separation. The Re–Re separation in Re 2 Br 4 (PMe 3 ) 4 is 0.12 Å larger than the one in Tc 2 Br 4 (PMe 3 ) 4 .…”
Section: Results and Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These were later shown , to contain instead Re 2 (O 2 CR) 4 2+ or Re 2 (O 2 CR) 3 Cl 2 + cations together with ReO 4 - anions. Just a few years ago, it was found that, on exposure to air, Re 2 Cl 4 (PMe 3 ) 4 gives rise to [Re 2 Cl 4 (PMe 3 ) 4 ]ReO 4 . Thus, the present observations are, in this respect at least, not unprecedented.…”
Section: Resultsmentioning
confidence: 99%
“…Several years ago, we began to take a systematic approach to elucidating the “rules of the game”, and we present here our latest report, wherein we deal with the simplest case (barring [Re 2 Cl 7 PR 3 ], where only one isomer 5 can exist), namely, [Re 2 Cl 6 (PR 3 ) 2 ]. To summarize briefly the position to date for cases where n = 2−4, we note that the most often characterized species are the 1,3,6,8 isomers ,4d, of the Re 2 X 4 (PR 3 ) 4 ( I ) molecules with a trans arrangement of phosphine ligands on each end of the molecule. The second isomer of that formula, namely, the 1,2,7,8 isomer, having PR 3 groups cis on each rhenium atom, was recently discovered by us 4a and is now known for three different phosphines. 4a-c Replacing one phosphine ligand by the halide in each of the isomers of I gives the isomeric compounds of composition [Re 2 X 5 (PR 3 ) 3 ] ( II ), namely, 1,2,7 and 1,3,6, both of which are now well established. 4b,e, Finally, for the [Re 2 X 6 (PR 3 ) 2 ] stoichiometry ( III ), the only form known so far corresponds to the centrosymmetric 1,7 arrangement. 4a,b, Neither the 1,2, 1,3, nor 1,6 isomers have yet been made.…”
Section: Introductionmentioning
confidence: 99%